Canadian Housing "Policy" in Perspective - Bacher, John (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1986)
This paper provides an overview of the history of Canadian housing policy, reviewing the origins of both the programs which were implemented as well as the options which were defeated. Canada's approach to housing policy is also compared to the manner in which other prosperous western democratic states have approached their housing problems. The paper finds that one of the ironies of Canadian housing policy is that homeownership assistance programs for middle income groups and subsidies for private investors have continually emerged in the midst of political demands for publicly subsidized rental housing for low income groups. The Canadian government's rigid commitment to an assisted market approach is exceptional in comparison with other western states. Starting in the 1930s a unity between government and business emerged while a wide gulf remained between federal housing officials and advocates of social housing. The paper argues that this tilt in Canadian housing policy in favour of those Canadians who are least in need of government assistance in securing decent accommodation is no accident, but reflective of the marketplace ethos that has shaped all federal housing efforts.